1986
DOI: 10.3109/02713688609000012
|View full text |Cite
|
Sign up to set email alerts
|

Lens proteins are substrates for the reticulocyte ubiquitin conjugation system

Abstract: In the aged lens postsynthetically altered molecules comprise the majority of lens proteins. Many proteolytic activities have been observed in lens supernatants. Since damaged or altered proteins are usually selectively and rapidly degraded in other cells and tissues, the accumulation of these species in the lens seemed enigmatic. Initiation of proteolysis has been studied most extensively in reticulocytes and ts 85 cells. In these systems proteolysis is absolutely ATP dependent, occurs effectively on high mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…We previously hypothesized that one role for the ubiquitin pathway is to remove damaged and cytotoxic proteins (3,40). In support of this hypothesis, data in Figs.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We previously hypothesized that one role for the ubiquitin pathway is to remove damaged and cytotoxic proteins (3,40). In support of this hypothesis, data in Figs.…”
Section: Discussionsupporting
confidence: 54%
“…Shortly after the discovery of the pathway (51,52), it was shown that some oxidized proteins are selectively degraded by this proteolytic pathway (18,53,54). Previously we demonstrated that 1) lens and retina tissues have ubiquitin-dependent proteolytic pathways (19,35,40,50,(55)(56); 2) oxidized lens proteins are selective substrates for the pathway (18); 3) efficiency of the pathway is related to cellular redox status (57); and 4) that lenses and lens epithelial cells in culture mount a robust ubiquitinylation response to oxidative stress (19,35 ubiquitinylation process are up-regulated in response to stress in these various experimental systems. The data in Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After heat shock, however, there is an increase in the amount and stability of Tritoninsoluble high molecular weight ubiquitin conjugates, suggesting an association with the cytoskeleton (34). Moreover, the rate ofprotein degradation decreases after heat shock (34,35) and during cellular aging (36,37). The increase in stable ubiquitin conjugates has been tentatively attributed to a saturation of the ubiquitin-mediated proteolytic system by an increased amount of altered proteins, as the ubiquitinating and ubiquitin-dependent proteolytic activities have been found to be maintained (34,38).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of the ubiquitin-acceptor proteins in these inclusions is likely to provide valuable insight into their mechanism of formation and to reveal the roles of the ubiquitin system in the pathology of the nervous system. which are known to occur with increased frequency during aging (37); it could also be due to sustained cellular stress related to the disease process, or to a combination of these events.…”
Section: Discussionmentioning
confidence: 99%